14. EXAMINATION AND TREATMENT AT AGRICULTURAL GENERAL HOSPITAL FROM APRIL 2019 TO MARCH 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: Analyze the structure of medical examination and treatment costs at Agriculture General Hospital from April 2019 to March 2022.Research subjects and methods: Cross-sectional description.Results: In 3 years (2019-2022), Agriculture General Hospital has welcomed 574,518 patients, inpatient treatment 102,586 times with disease models of 22 disease chapters according to the international statistical classification of diseases disabilities and related health problems. Average treatment costs for each hospitalization: circulatory system diseases have the highest average treatment costs at nearly 9 million VND; the lowest is unclassified clinical and paraclinical symptoms and abnormalities with more than 2.8 million VND. Average cost per outpatient medical examination: musculoskeletal, joint and connective tissue diseases have the highest average outpatient medical examination and treatment cost per visit at 413,006 VND; the lowest is eye and adnexal diseases with 90,208 VND.Conclusion: Analyzing inpatient and outpatient treatment costs for patients coming for examination and treatment at Agriculture General Hospital has supported tracking and monitoring the use of funding and evaluating effectiveness of implemented activities as well as to serve planning, budgeting and identifying additional resources needed for the hospital is one of the issues of special concern and high efficiency.
Keywords: Medical examination costs; inpatient treatment costs; outpatient treatment costs